The gut-skin axis: a bi-directional, microbiota-driven relationship with therapeutic potential - Maira Jimenez-Sanchez; Larissa S. Celiberto; Hyungjun Yang; Ho Pan Sham; Bruce A. Vallance (Gut Microbes)
This review explores the emerging term “gut-skin axis” (GSA), describing the bidirectional signaling that occurs between the skin and the gastrointestinal tract under both homeostatic and disease conditions. Central to GSA communication are the gut and skin microbiota, the microbial communities that colonize these barrier surfaces. By influencing diverse host pathways, including innate immune, vitamin D receptor, and Aryl hydrocarbon receptor signaling, a balanced microbiota contributes to both tissue homeostasis and host defense. In contrast, microbiota imbalance, or dysbiosis at one site, can lead to local barrier dysfunction, resulting in the activation of signaling pathways that can disrupt tissue homeostasis at the other site, potentially leading to inflammatory skin conditions such as atopic dermatitis and psoriasis, or gut diseases like Inflammatory Bowel Disease. To date, most research on the GSA has examined the impact of the gut microbiota and diet on skin health, but recent studies show that exposing the skin to ultraviolet B-light can beneficially modulate both the gut microbiome and intestinal health. Thus, despite the traditional focus of clinicians and researchers on these organ systems as distinct, the GSA offers new opportunities to better understand the pathogenesis of cutaneous and gastrointestinal diseases and promote health at both sites.